PEER TUTORING: EXPLORING THE EFFECTS ON LEARNING GRADE 9 MATHEMATICS - Berso, Liezel B; Lorente, Richard M (PEOPLE: International Journal of Social Sciences, 2020)
This descriptive-comparative study aimed to develop session plans with learning activities for peer tutoring on quadratic equations. It involved five classes of Grade 9 students of Bantayan National High School, Tabaco City, Albay, Philippines wherein one class was randomly selected as the peer tutored group while the remaining four classes were considered the non-peer tutored groups. The peer tutoring sessions were conducted during the Independent/Cooperative Learning (ICL) period. The sources of data included the students’ reflection entries, observation notes, responses from focus group discussions, and periodic examination results. Findings showed that there were nine session plans with learning activities developed with the integration of cooperative and contextualized learning approaches. The peer tutors were able to master the lessons since they have the opportunity to study it again and revise what they have learned. They also gained more friends, boosted their confidence, and became more interested and enthusiastic in learning and teaching Mathematics together with their peer tutees. On the other hand, the peer tutees grasped the lessons because their tutor gave immediate feedback to them. They also learned how to cooperate and participate with their group to achieve their goal. It was also showed that the peer tutees were very much engaged and eager to learn during the peer tutoring. These were some of the significant learning experiences of the peer tutors and peer tutees during the conduct of peer tutoring. In terms of performance, based on the results of their periodic examination, the peer tutored group had a better performance than those non-peer tutored groups. The session plans with learning activities for peer tutoring were then concluded to give benefits in the learning experiences and enhanced the Mathematics performance of the learners.